Modélisation et simulation d’un générateur asynchrone à turbine éolienne - OUBBICHE Mahieddine, Mahieddine; ABIKCHI, Mohammed (University of El Oued جامة الوادي, 2018)
The work carried out concerns a study of an electric power supply system for two types of loads, one main and the other secondary, and this by two types of electric sources. The first source is a wind turbine and the second is a variable speed diesel generator that works as a complement to ensure continuity of power supply by electricity in terms of presence and value. the system simulation was done, and all the results are done and interpreted. يهتم العمل بدراسة إمداد الطاقة الكهربائية لنوعين من الأحمال ، واحدة والأخرى ثانوية ، ونوعان من المصادر الكهربائية. المصدر الأول هو توربينات الرياح والثاني هو مولد ديزل متغير السرعة يعمل كمكمل لضمان استمرارية إمدادات الطاقة عن طريق الكهرباء من حيث الوجود والقيمة. تم إجراء محاكاة النظام ، ويتم تنفيذ جميع النتائج وتفسيرها.
مذكرة ماسترهندسة ميكانيكية تخصص إلكتروميكانيك
Keywords: diesel generator, wind turbine, synchronous generator, asynchronous generator; مولد الديزل ، توربينات الرياح ، مولد متزامن ، مولد غير متزامن